1997
DOI: 10.1017/s002202999600194x
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of clinical mastitis manifestations in Danish organic dairy herds

Abstract: Danish organic dairy production is characterized by a low input of antibiotics for udder treatment and a high input of other mastitis control procedures. A study was conducted in 14 organic dairy herds with the objectives of obtaining a comprehensive description of clinical mastitis cases and identifying characteristic patterns in these results. Clinical signs, inflammatory reactions and microbiological identifications were obtained from 367 cases of clinical mastitis occurring over 18 months. Cow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 0 publications
4
35
0
Order By: Relevance
“…It also includes low incidence of clinical mastitis, minimize potential hazards for human health such as prevention of residues in milk, potential transfer of antibiotic resistance to human pathogens, and transfer of pathogens through dairy products. Addressing consumer demands with regard to product safety, transmission of infectious diseases, welfare and eco-system health [56] becomes a constraint on the dairy production systems. It is therefore inevitable that more complete udder health programs and monitoring systems have been developed and implemented.…”
Section: Resultsmentioning
confidence: 99%
“…It also includes low incidence of clinical mastitis, minimize potential hazards for human health such as prevention of residues in milk, potential transfer of antibiotic resistance to human pathogens, and transfer of pathogens through dairy products. Addressing consumer demands with regard to product safety, transmission of infectious diseases, welfare and eco-system health [56] becomes a constraint on the dairy production systems. It is therefore inevitable that more complete udder health programs and monitoring systems have been developed and implemented.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the response time to infection may vary according to the pathogenic variability of the strains and their resistance to antibiotics, as well as to the animals' own resistance. That variability was especially revealed with Streptococcus uberis [22,26,37].…”
Section: Discussionmentioning
confidence: 99%
“…The difference between considering one (23.2%) or two controls (21.2%) is small and would include both incorrectly diagnosed udder quarters and short duration mastitis. In spite of the difficulties to compare data, particularly for gram-negative microorganisms, most studies, both in conventional and organic farms, have shown lower mastitis rates than in our organic farms (Hovi & Roderick, 1998;Vaarst, 2001;Lopez-Villalobos et al, 2003;Sato et al, 2005;Piepers et al, 2007;Ruegg, 2009).…”
Section: Intramammary Infection Dynamicsmentioning
confidence: 99%